Norcantharidin Inhibits cell growth by suppressing the expression and phosphorylation of both EGFR and c-Met in human colon cancer cells. Issue 1 (December 2017) - Qiu, Peiju; Wang, Siwen; Liu, Ming; Ma, He; Zeng, Xuan; Zhang, Meng; Xu, Lingling; Cui, Yidi; Xu, Huixin; Tang, Yang; He, Yanli; Zhang, Lijuan
Abstract Background Norcantharidin (NCTD) is a Chinese FDA approved, chemically synthesized drug for cancer treatment. The effect of NCTD on signaling proteins of EGFR and c-Met was systematically elucidated in current study. Methods Two human colon cancer cell lines, HCT116 and HT29, were used as model systems to investigate the anti-cancer molecular mechanism of NCTD. Cell cycle arrest and early/late apoptosis were analyzed by flow cytometry. The levels of EGFR, phospho-EGFR, c-Met, phospho-c-Met and other related proteins were quantified by western blot analysis. Results NCTD induced cell cycle arrest at G2/M phase in both cell lines. The early and late apoptosis was also observed. Further investigation indicated that NCTD suppressed not only the expression of the total EGFR and the phosphorylated EGFR but also the expression of the total c-Met and the phosphorylated c-Met in colon cancer cells. Moreover, EGFR expression could be mostly restored by co-treatment with MG132, a proteasome inhibitor. In addition, NCTD-induced cell death was comparable to that of the anti-cancer drug gefitinib, a tyrosine kinase inhibitor for EGFR, based on the immunoblot analysis of the expressed proteins after the drug treatment. Conclusions NCTD might be a useful and inexpensive drug candidate to substitute for gefitinib to serve the treatment needs of cancer patients.